DYNAMICS OF FORMATION OF PIGMENT SUBSTANCES IN LEAVES OF DURUM SPRING WHEAT DEPENDING ON THE DIFFERENT COENOSIS VOLTAGE BETWEEN PLANTS IN THE CROPS - Рожков, А. О.; Пузік, В. К. (Scientific Progress & Innovations, 2013)
The results of the three-year study (2008–2010) to determine the dynamics of the formation of photosynthetic pigments in plants of durum spring wheat varieties Kharkiv 41, depending on the different ways of planting and seeding rate are given in the article. A significant effect of the studied elements of the technology on the content of chlorophyll and carotenoids in the leaves of plants was found. The content of photosynthetic pigments was changed to a large extent at the impact factor of the seeding rate. The general regularity was to reduce the content of chlorophyll and carotenoids in the leaves of plants at effective seeding rate and optimization of the distribution of plants over the area of ​​nutrition. The studies identified a direct correlation between the content of pigments and grain productivity of the ear of the main shoot of the plant.